Dyslipidemia rather than Type 2 Diabetes Mellitus or Chronic Periodontitis Affects the Systemic Expression of Pro- and Anti-Inflammatory Genes - Rafael Nepomuceno; Bárbara Scoralick Villela; Sâmia Cruz Tfaile Corbi; Alliny De Souza Bastos; Raquel Alves Dos Santos; Catarina Satie Takahashi; Silvana Regina Perez Orrico; Raquel Mantuaneli Scarel-Caminaga (Mediators of Inflammation)
A high percentage of type 2 diabetes mellitus (T2D) patients are also affected by dyslipidemia and chronic periodontitis (CP), but no studies have determined the gene expression in patients that are simultaneously affected by all three diseases. We investigated the systemic expression of immune-related genes in T2D, dyslipidemia, and CP patients. One hundred and fifty patients were separated into five groups containing 30 individuals each: (G1) poorly controlled T2D with dyslipidemia and CP; (G2) well-controlled T2D with dyslipidemia and CP; (G3) normoglycemic individuals with dyslipidemia and CP; (G4) healthy individuals with CP; (G5) systemic and periodontally healthy individuals. Blood analyses of lipid and glycemic profiles were carried out. The expression of genes, including IL10, JAK1, STAT3, SOCS3, IP10, ICAM1, IFNA, IFNG, STAT1, and IRF1, was investigated by RT-qPCR. Patients with dyslipidemia demonstrated statistically higher expression of the IL10 and IFNA genes, while IFNG, IP10, IRF1, JAK1, and STAT3 were lower in comparison with nondyslipidemic patients. Anti-inflammatory genes, such as IL10, positively correlated with parameters of glucose, lipid, and periodontal profiles, while proinflammatory genes, such as IFNG, were negatively correlated with these parameters. We conclude that dyslipidemia appears to be the primary disease that is associated with gene expression of immune-related genes, while parameters of T2D and CP were correlated with the expression of these important immune genes.